Performance management system (PMS) as a predictor of employee performance of private bank managers in (Pakistan) - Fareed, Muhammad; Mohd Isa, Mohd Faizal; Ahmad, Aqeel; Laeeq, Hood (Medwell Journal, 2016)
The aim of this study is to explore the influence of Performance Management System (PMS) on managers’ performance of Meezan bank in Lahore (Pakistan).PMS is mostly undertaken to let management know the performance of employees since employees’ performance is one of the considerable issues for the organizations in this competitive world.A total of 115 survey questionnaires were distributed through mail to the managers of Meezan bank using simple random sampling and 61 responses were returned which makes 53% response rate. Instrument was developed by the researchers with the help of HRM experts and initially pilot test was done to test the reliability of the instrument which showed all alpha values were greater than 0.80.Pearson correlation, linear regression, mean and S.D techniques were used to check the relationship between predictors and dependent variable.According to findings, all the predictors “job dimension, clear goals and objectives, performance appraisal system and rewards and recognition” have significant relationship with performance of managers of Meezan bank (Lahore).It is proposed that top management of Meezan bank should considerably look at the formal implementation of the PMS for sustaining competitive advantage.